Field aging declines the regulatory effects of biochar on cadmium uptake by pepper in the soil. (1st November 2022) - Xing, Dan; Cheng, Hongguang; Ning, Zengping; Liu, Yizhang; Lin, Shan; Li, Yongfu; Wang, Xi; Hill, Paul; Chadwick, Dave; Jones, Davey L.
Abstract: Biochar application is not only being widely promoted as an ideal strategy to mitigate global climate warming, but it also has the advantage of reducing heavy metal bioavailability and migration in the soil. However, studies on the effects of field aging on biochar to reduce heavy metals from the soil are still limited. The present study aimed to explore the effects and mechanisms of aged biochar added to the soil planted with pepper plants on cadmium (Cd) uptake. To achieve this, un-amended soil (control), soil amended with fresh biochar, and aged biochar (biochar recovered from a long-term field trial after 9 years) were used to investigate the effects of field aging on biochar adsorption efficiency. The results revealed that the amount of Cd in the plant planted in control soil, amended with fresh and aged biochar, accounted for 40 ± 6.10, 17.18 ± 1.19, and 18.68 ± 0.79, respectively. There was a significant difference ( P < 0.05 ) in the amount of Cd that was uptaken by plants among all treatments. However, soil amended with fresh biochar significantly ( P < 0.05 ) decreased the amount of Cd in plants compared with soil amended with aged biochar. This indicates that field aging declines the potential of biochar to lower heavy metal bioavailability and retention in the soil. This study demonstrates that long-term burial lessens the ability of biochar to interact with Cd and suggests that biochar amendment can lower Cd in the soil, depending on the freshness and aging of biochar. Highlights: The aging effect of biochar decrease the adsorption to Cd. Aged biochar reduced the uptake of Cd by plant. Biochar aging weakens the effect of biochar heavy metal remediation.